THE RELATIONSHIP BETWEEN JOB STRESS AND PSYCHOLOGICAL WELL-BEING IN DIGITAL NOMADS - Uşak, Hatice; Erkutlu, Hakan (International Scientific Journal Vision, 2025)
Globalization and the rapid development of technology have led to major changes in working life, and this transformation has brought the concept of "digital nomadism" into our lives. Digital nomads are individuals who can work without being bound by geographical boundaries and live freely in different parts of the world thanks to the internet and mobile technologies. While this lifestyle offers freedom, flexibility, and the opportunity to experience different cultures, it can also bring challenges, such as job stress, social isolation, and psychological well-being. This study aims to examine the relationship between job stress and psychological well-being levels of digital nomads and to understand how demographic factors play a role in this relationship. Forty digital nomads from countries such as Turkey, Germany, India, Venezuela, Italy, France, Spain, England, Australia, Australia, and Pakistan participated in the study. Data were collected using a survey method and analyzed using job stress and psychological well-being scales. The findings show that there is a significant relationship between the psychological well-being of digital nomads and job stress. On the other hand, it was determined that demographic variables such as age, gender, education level, and marital status do not moderate this relationship. This research contributes to understanding the dynamics between work stress and psychological well-being, especially by revealing the opportunities and challenges of digital nomadism. At the same time, it aims to shed light on future studies in this field by emphasizing the effect of demographic factors such as age on psychological well-being.